Attitudes towards suicide in urban and rural China: a population based, cross-sectional study. Issue 1 (December 2016) - Zou, Yaming; Leung, Ricky; Lin, Shao; Yang, Mingan; Lu, Tao; Li, Xianyun; Gu, Jing; Hao, Chun; Dong, Guanghui; Hao, Yuantao
Abstract Background Suicide intervention programs have been guided by findings that attitude towards suicide and suicidal behavior may be causally linked. These findings also make it imperative to identify the factors that influence attitudes towards suicide. However, there has been little research on attitudes towards suicide among the general population, especially in low-income and middle-income countries. This population-based, cross-sectional study investigated the associated factors of attitudes towards suicide among a representative sample of urban and rural adult residents in China. Methods A multi-stage, stratified random sampling approach was implemented to select participants. Data were collected by a survey using the Scale of Public Attitudes about Suicide (SPAS). The survey also collected some socio-demographic factors and suicidal history of participants. Statistical tests were conducted to identify associated factors that account for variations in attitudes towards suicide. Results The residents in China generally hold a neutral attitude towards suicide. Attitudes towards suicide among Chinese residents were associated with age, duration of formal education, marital status, job and suicidal ideation. Different attitudinal subscales seemed not to share the same risk factors. However, gender, ethnicity, religious belief, housing style and economic status might not influence residents' attitudes towards suicide. Attitudes towards suicide among Chinese urban and rural residents generally had no statistical difference with one notable exception: opinions on whether or not suicides and suicide attempts are different phenomena. Conclusions Age, duration of formal education, marital status, job and suicidal ideation seem to have an impact on attitudes towards suicide among residents. Urban and rural residents have similar attitudes towards suicide with the only statistically significance difference being their opinions on whether or not suicides and suicide attempts are different phenomena.